AB0579 Behcet's Disease and Pregnancy. May Recurrent Fever Suggest A Disease Subset with Different Outcome?. (10th June 2014) - Marconato, M.; Sfriso, P.; Schiavon, F.; Caso, F.; Cantarini, L.; Brizi, M.G.; Doria, A.; Agostini, C.; Tognon, S.; Punzi, L.; Marcolongo, R.
Abstract : Background: BD is a systemic vasculitis with different subsets of clinical manifestations (1). The recurrent fever, detectable only in a subgroup of patients, along with the relapsing course of disease, the presence of signs and symptoms typical of autoinflammatory syndromes, the good response to anti-cytokines treatment and the increasing detection of mutations in genes encoding for molecules involved in innate-immunity regulation suggest to consider a subgroup of BD as auto-inflammatory disease (2). Objectives: The aim of this study was to understand weather different disease subsets may correlate with the great variability observed in obstetric outcome and disease activity during pregnancy (3). Methods: All patients affected with BD, according to diagnostic criteria (1), who experienced at least one pregnancy and seen in four Italian referral centers (Rheumatology Unit of Padua, Clinic Immunology Unit of Padua, Ophthalmology Unit of Padua, Rheumatology Unit of Siena) were included in the study. Data regarding fetal and maternal outcome was retrospective collected by researchers with clinical interviews based on a common questionnaire. Pregnancies were sub-divided into two groups: group 1 included patients with recurrent fever, while group 2 included patients without recurrent fever. Recurrent fever has been previously defined as three or more episodes of fever of unknown origin per year. Results: 36 women affected with BD reported 71 pregnancies and 60 newborns. Group 1 included 13 patients and 24 pregnancies. 23 pregnancies occurred after the disease onset, while in 1 case BD started during pregnancy. Group 2 included 23 patients and 47 pregnancies. 24 pregnancies occurred after the disease onset, while 22 occurred before the disease onset. One case of BD started during pregnancy. Mean of disease duration was 16 years in group 1 and 11 years in group 2. Febrile BD started before pregnancy more often than not febrile: 83% vs 52%, p=0, 008. Regarding disease activity during pregnancy, we observed (group 1 vs group2): stable disease activity 45% vs 20%, increased disease activity 40% vs 8%, improved disease activity 10% vs 8%, complete remission 5% vs 64%, p=0, 003. As for pregnancy complications, we recorded (group 1 vs group 2): gestational hypertension 29, 1% vs 0, p=0, 001, preeclampsia 20, 8% vs 0 p=0, 001, miscarriage 20, 8% vs 12, 7% and preterm delivery 8, 3% vs 6, 4%. Conclusions: Febrile BD activity remains unaffected or it worsens during pregnancy, while not febrile BD usually improves, even to a complete remission. Patients with recurrent fever have an higher risk of gestational complications than patients without recurrent fever, particularly gestational hypertension and preeclampsia. References: Saadoun D, Wechsler B, Behçet's disease, Orpahnet J Rare Dis, (2012) 7-12 Jirino Y et all, Targeted resequencing implicates the familial Mediterranean fever gene MEFV and toll-like receptor 4 gene TRL4 in Behçet disease, PNAS (May 14, 2014) vol. 110, no. 20 Gatto M, Iaccarino L, Canova M, Zen M, Nalotto L, Ramonda R, Punzi L, Doria A, Pregnancy and vasculitis: A systematic review of the literature, Autoimmunity Reviews 11 (2012) A447–A459 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4502